Professional Flip-Pdf-Based Interactive Modules to Enhance The Creative Thinking Skills and Collaborative Skills of High School Students - Almira Rayyah Shadriah Fahru; Kundera, I Nengah; Mursito S. Bialangi (LPPM Undiksha, 2024)
The ability of students to think creatively and collaboratively is not optimal because the learning atmosphere is not interactive and lacks variety in the use of learning media. This research aims to develop interactive e-module learning media based on flip-pdf-professional that can improve students' creative thinking skills and collaborative skills. The method used in research is research and development with a 4D development model (define, design, develop, and disseminate). Data were collected using observation, interview, questionnaire, and test methods. Descriptive, qualitative, and quantitative data analysis. The results showed that the flip-pdf-professional-based interactive E-module product is valid and very practical to use in biology learning in senior high school. The E-module product developed is quite effective in improving students' creative thinking skills and collaborative skills in biology learning. Research on the development of interactive e-modules based on flip-pdf-professional is more practical for teachers to use in learning and helps students with independent learning.